Productivity benefits of minimally invasive surgery in patients with chronic sacroiliac joint dysfunction - Saavoss JD; Koenig L; Cher DJ (Dove Medical Press, 2016)
Josh D Saavoss,1 Lane Koenig,1 Daniel J Cher2 1KNG Health Consulting, LLC, Rockville, MD, 2SI-BONE, Inc., San Jose, CA, USA Introduction: Sacroiliac joint (SIJ) dysfunction is associated with a marked decrease in quality of life. Increasing evidence supports minimally invasive SIJ fusion as a safe and effective procedure for the treatment of chronic SIJ dysfunction. The impact of SIJ fusion on worker productivity is not known. Methods: Regression modeling using data from the National Health Interview Survey was applied to determine the relationship between responses to selected interview questions related to function and economic outcomes. Regression coefficients were then applied to prospectively collected, individual patient data in a randomized trial of SIJ fusion (INSITE, NCT01681004) to estimate expected differences in economic outcomes across treatments. Results: Patients who receive SIJ fusion using iFuse Implant System® have an expected increase in the probability of working of 16% (95% confidence interval [CI] 11%–21%) relative to nonsurgical patients. The expected change in earnings across groups was US $3,128 (not statistically significant). Combining the two metrics, the annual increase in worker productivity given surgical vs nonsurgical care was $6,924 (95% CI $1,890–$11,945). Conclusion: For employees with chronic, severe SIJ dysfunction, minimally invasive SIJ fusion may improve worker productivity compared to nonsurgical treatment. Keywords: sacroiliac joint fusion, low back pain, sacroiliac joint pain, clinical trial, health care costs, indirect costs